Complete loss of HLA class I antigen expression on melanoma cells: A result of successive mutational events - Paschen, Annette; Sucker, Antje; Song, Mingxia; Schadendorf, Dirk (International journal of cancer, 2003)
Alterations in the surface expression of HLA class I molecules have been described as a strategy of tumors to evade recognition by cytotoxic T cells. We detected complete loss of HLA class I antigen presentation for 2 tumor cell lines from 1 melanoma patient, the first originated from a regional lymph node lesion diagnosed simultaneously with the primary tumor and the second established 8 months later from a metastatic pleural effusion sample. Antigen presentation was not inducible with IFN-γ but could be restored after transfection of tumor cells with b2m cDNA, indicating a defect in b2m expression. Analysis of the nature of this defect revealed that it originated from at least 2 mutational events affecting both copies of the b2m gene: a microdeletion of 498 bp in one b2m gene, including its entire exon 1, and a macrodeletion involving the entire copy of the second b2m gene. Microsatellite analysis pointed to the macrodeletion by demonstrating LOH for several specific markers on the long arm (q) of chromosome 15. Structural imbalance of 15q was verified by FISH. FISH studies also indicated the coexistence of a structurally abnormal variant of chromosome 15q with 2 apparently entire chromosomes 15q harboring the homozygous b2m microdeletion. Block of b2m expression in tumor cells builds a barrier to immunotherapy of cancer patients, and its early incidence should be of major consideration in the development and design of immunotherapeutic strategies. © 2002 Wiley-Liss, Inc.
First published: 12 December 2002
Gesehen am 17.11.2020